2022
DOI: 10.1186/s12974-022-02466-2
|View full text |Cite
|
Sign up to set email alerts
|

High-fat diet exacerbates cognitive decline in mouse models of Alzheimer's disease and mixed dementia in a sex-dependent manner

Abstract: Background Approximately 70% of Alzheimer’s disease (AD) patients have co-morbid vascular contributions to cognitive impairment and dementia (VCID); this highly prevalent overlap of dementia subtypes is known as mixed dementia (MxD). AD is more prevalent in women, while VCID is slightly more prevalent in men. Sex differences in risk factors may contribute to sex differences in dementia subtypes. Unlike metabolically healthy women, diabetic women are more likely to develop VCID than diabetic men… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 86 publications
2
29
0
Order By: Relevance
“…Additionally, there are known differences between males and females in terms of immune function and inflammation ( 81 , 82 ), including in microglia ( 83 ). These differential effects also potentially impact cognition, as some have shown a differential effect of sex on cognitive outcomes ( 84 ). As mentioned above, no differences were observed between groups for puzzle box performance.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, there are known differences between males and females in terms of immune function and inflammation ( 81 , 82 ), including in microglia ( 83 ). These differential effects also potentially impact cognition, as some have shown a differential effect of sex on cognitive outcomes ( 84 ). As mentioned above, no differences were observed between groups for puzzle box performance.…”
Section: Discussionmentioning
confidence: 99%
“…The prevention, diagnosis and treatment of gliosis must be addressed in patients with obesity, and especially in those who have metabolic comorbidities, points included in this review. Gliosis, if left untreated, can increase the risk of long-term neurodegeneration [ 5 ]. The pathophysiology of gliosis includes the increase in free radicals, which perpetuate neuroinflammation [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been accepted that the hippocampus is the main functional area responsible for learning and memory; hippocampus dysfunction is considered to be a key and central mechanism that underlies cognitive impairment (Gannon et al, 2022 ). Of course, neuronal synaptic plasticity has long been considered an important component and the neural basis of learning and memory (Neves et al, 2008 ), and it has been reported that HFD can damage the synaptic plasticity in the hippocampal neurons of obese mice (O'Brien et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%